2018
DOI: 10.1097/md.0000000000010956
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with overweight and obesity in HIV-infected people

Abstract: Identifying risk factors associated with overweight and obesity in HIV-infected patients.A cross-sectional study analyzing data from patients attending an HIV outpatient unit. Overweight was defined as body mass index (BMI) ≥25 kg/m2; <30 kg/m2, obesity was ≥30 kg/m2. Patients’ characteristics contemporary to BMI assessment were collected. Multivariate logistic regression identified risk factors associated with overweight/obesity.Eight hundred sixty-two patients, median age 51 years, 21.5 years of HIV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…ART suppresses viral replication and increases CD4 count resulting in the restoration of recipients' health status [25]. us, the BMI change observed among the recipients herein might result from a natural process or interplay of different factors [11,15,26]. By preventing the advancement of HIV infection, ART allows other bodily processes to proceed normally and increase the recipients' weight.…”
Section: Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…ART suppresses viral replication and increases CD4 count resulting in the restoration of recipients' health status [25]. us, the BMI change observed among the recipients herein might result from a natural process or interplay of different factors [11,15,26]. By preventing the advancement of HIV infection, ART allows other bodily processes to proceed normally and increase the recipients' weight.…”
Section: Characteristicsmentioning
confidence: 99%
“…However, a study by Todd and colleagues [10] unearthed associations between Nucleoside Reverse Transcriptase Inhibitors (NRTI) and increased odds of hyperinsulinemia, whereas cumulative exposure to Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTI) or PI drugs lacked association with insulin resistance markers or correlates of DRC and overweight/obesity. Recent work by Obry-Roguet and co-workers [11] failed to identify any association between all ART combinations and overweight/obesity. eir results partly support previous reports by Hasse and colleagues [12] that only limited associations existed between ART and overweight/obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the normal weight group had a longer median period of ART than patients with overweight or obesity. Previously, a cross-sectional study with 862 patients with 21.5 years of HIV infection follow-up also concluded that the prevalence of overweight and obesity was not influenced by the duration of infection ( 64 ). A meta-analysis on the association of ART with overweight/obesity also did not find a significant association ( 64 ).…”
Section: Discussionmentioning
confidence: 98%
“…Previously, a cross-sectional study with 862 patients with 21.5 years of HIV infection follow-up also concluded that the prevalence of overweight and obesity was not influenced by the duration of infection ( 64 ). A meta-analysis on the association of ART with overweight/obesity also did not find a significant association ( 64 ). In contrast, other studies showed a higher BMI in patients who received ART ( 65 ), with significant weight gain after starting ART ( 3 , 66 ).…”
Section: Discussionmentioning
confidence: 98%